The Effect of Work-Life Balance and Employment Status on the Commitment of Ar-Royan Tasikmalaya Confection Production Department Employees - Rosmaya, Ledi; Ramadhani, Indi; Nur Fahmi Mufreni, Alfin (Ann Publisher, 2023)
The objectives of this study were to determine and analyze work-life balance, employment status, employee commitment and the effect of work-life balance and employment status on employee commitment in the production division of Ar-royan Tasikmalaya Confectionery. The research method used was the survey method, while the sampling method uses the census method. Data collection techniques were used for primary data through questionnaires from 63 respondents and interviews, secondary data from literature review and the company. The analysis tool uses path analysis. The results showed that work-life balance was included in the high classification, employment status in the high classification, and employee commitment in the high classification. Partially, work-life balance and employment status positively affect employee commitment. Work-life balance and employment status simultaneously affect employee commitment.